Social Justice in Public Services: Evaluating Access and Inclusion for Vulnerable Groups - Irmawati Irmawati; Anita Syam; Andi Asrijal (Socious Journal, 2026)
Social justice in public service delivery has become a critical issue, particularly in addressing inequalities faced by vulnerable groups in accessing essential services. This study aims to evaluate how access and inclusion influence the realization of social justice in public services. A mixed-method explanatory approach was employed, combining quantitative data from structured questionnaires and qualitative insights from in-depth interviews involving vulnerable populations. The quantitative data were analyzed using Structural Equation Modeling (SEM-PLS), while qualitative data were examined through thematic analysis to identify key barriers and inclusion strategies. The findings indicate that access to public services significantly influences inclusion, and inclusion plays a crucial role in achieving social justice outcomes. Administrative barriers were found to negatively affect both access and inclusion, highlighting the importance of institutional reforms. The results also reveal that inclusion mediates the relationship between access and social justice, emphasizing that equitable outcomes depend not only on availability but also on fair treatment and participation. In conclusion, this study demonstrates that achieving social justice in public services requires an integrated approach that combines improved access with inclusive practices. Policymakers must prioritize user-centered service design and equity-oriented strategies to ensure that vulnerable groups are not left behind.